Advertising Media Strategy as Product Ordering - Mahyuni Hidayat; Bornea Retno Mahalayati; Hanil Sadikin; Syahrial Shaddiq; H M. Zainul (Institute of Computer Science (IOCS), 2021)
With the splendor of advertising through above the line and the line bellows, then a separate issue for producers and advertising agencies to be able to create an effective to attract the attention of consumers on a product. And can be effective, if the purpose of advertising can be achieved or accomplished and useful for companies in the implementation of marketing functions, so a advertising be flexible, stable, sustainable, simple, and easy to understanding. Can create effective advertising is, of course, must begin with an understanding of the advertised product marketing programs, in addition to the ad should creative, has appeal, credibility endorse be aware of recall advertising is part of marketing activities. Through promotional activities, advertising is one of the strategies in marketing communications, to introduce or explain the product is marketed. Strategy that is often used in the shooting target market is the grouping of market/segment as an area prospective buyers/users. Selection of a specific market group will be easier to communicate through media advertising products. Or character traits in a group is a market segment of data to facilitate market the product. Market segment the reference and the main purpose of the products offered through advertising. Therefore, in designing advertising must understand and know what is happening in the market as a place of pitching products.